STUDENTS’ ERRORS IN USING LEXICOGRAMMATICAL FEATURES IN WRITING RECOUNT TEXT (A Study at the X Grade Students of SMA Negeri 4 Padangsidimpuan 2016/2017 Academic Year) - Asriani Hasibuan; Trifo Maida Simatupang (Elite : English and Literature Journal, 2018)
The objectives of this research are to know the students’ errors in using lexicogrammatical features in writing recount text at tenth grade students of SMA Negeri 4 Padangsidimpuan and to know why the students made errors in using lexico grammatical features in writing recount text and  to know how the efforts done by the English teacher to overcome difficulties of students in using lexicogrammatical features in writing recount text. The informants of this research are six students from X-4 class. The method which is used in this research is descriptive analysis. Firstly, students were given test which had to choose one of the topics, the students wrote a recount text based on the topics chosen and the writer collected their papers then analyzed it. The result of this research is finding errors in proper noun, pronoun, past tense, adjective, action verbs, conjunction and time connective then adverb. But, the most common errors which found is are using past tense, using pronoun and using adjective (adjective order). The causes of students’ errors in using lexicogrammatical features in writing recount text is carelessness (lack motivation), first language interference and translation (word by word) and the efforts of English teacher to overcome the difficulties in using lexicogrammatical features in writing recount text is by doing repetition in teaching recount text especially lexicogrammatical feature, using demonstration method, using media, and the last is always giving task and homework at the end of every meet.Keywords : Error Analysis, Recount Text, Lexicogrammatical Features, Writing.Abstrak        Penelitian ini bertujuan untuk mengetahui kesalahan siswa dalam menggunakan fitur leksikogrammatik dalam menulis teks recount pada siswa kelas X SMA Negeri 4 Padangsidimpuan dan untuk mengetahui mengapa siswa membuat kesalahan dalam menggunakan fitur lexicogrammatical dalam menulis teks recount dan untuk mengetahui bagaimana upaya yang dilakukan oleh guru bahasa Inggris untuk mengatasi kesulitan siswa dalam menggunakan fitur lexicogrammatical dalam menulis teks recount. Informan penelitian ini adalah enam siswa dari kelas X-4. Metode yang digunakan dalam penelitian ini adalah analisis deskriptif. Pertama, siswa diberi tes yang harus memilih salah satu topik, siswa menulis teks recount berdasarkan topik yang dipilih dan penulis mengumpulkan kertas mereka kemudian menganalisanya. Hasil dari penelitian ini adalah menemukan kesalahan dalam kata benda, kata benda, past tense, kata kerja, verba aksi, konjungsi, dan waktu konektif kemudian kata keterangan. Tapi, kesalahan paling umum yang ditemukan adalah menggunakan bentuk lampau, menggunakan kata ganti dan menggunakan kata sifat (kata sifat). Penyebab kesalahan siswa dalam menggunakan fitur lexicogrammatical dalam menulis teks recount adalah kecerobohan (kurangnya motivasi), gangguan bahasa pertama dan terjemahan (kata demi kata) dan upaya guru bahasa Inggris untuk mengatasi kesulitan dalam menggunakan fitur lexicogrammatical dalam menulis teks recount adalah dengan melakukan pengulangan dalam mengajar teks recount terutama fitur lexicogrammatical, menggunakan metode demonstrasi, menggunakan media, dan yang terakhir selalu memberikan tugas dan pekerjaan rumah pada setiap akhir pertemuan.Kata Kunci: Analisis Kesalahan, Teks Recount, Fitur Leksikogrammatik, Menulis